Agroecology Initiative Business Incubator Program. Business model: Jamm Bugum Bakery - Fall, Modou; Sene, Mame Birame; Pireaux, Marc; Camara, Astou Diao; Cesaro, Jean-Daniel (2024)
As part of its support for local initiatives, the CGIAR Initiative on Agroecology, through its third component WP3, dedicated to the development of value chains within the framework of the business incubation program supported the increase of the production and marketing capacity of the bakery, in order to strengthen its socio-economic impact, particularly in terms of income generated and jobs created.